Correction: The role of artificial photo backgrounds of shelter dogs on pet profile clicking and the perception of sociability. - Fiona Lamb; Allison Andrukonis; Alexandra Protopopova (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0255551.].